Immune targeting of three independent suppressive pathways (TIGIT, PD-L1, TGFβ) provides significant antitumor efficacy in immune checkpoint resistant models. (31st December 2022) - Franks, S. Elizabeth; Fabian, Kellsye P.; Santiago-Sánchez, Ginette; Wolfson, Benjamin; Hodge, James W.
ABSTRACT: Immune checkpoint blockade (ICB) therapy, while groundbreaking, must be improved to promote enhanced durable responses and to prevent the development of treatment-refractory disease. Cancer therapies that engage, enable, and expand the antitumor immune response will likely require rationally designed combination strategies. Targeting multiple immunosuppressive pathways simultaneously may provide additional therapeutic benefit over singular targeting. We therefore hypothesized that the use of two molecules which inhibit three independent, but overlapping, pathways (TIGIT:CD155, PD-1/PD-L1, and TGFβ) would provide significant antitumor efficacy in the syngeneic ICB resistant colorectal tumor model MC38 expressing human carcinoembryonic antigen (CEA) in CEA transgenic mice. This novel combination treatment strategy has significant antitumor activity and survival benefit in two models of murine carcinomas, MC38-CEA (CRC) and TC1 (HPV + lung carcinoma). MC38-CEA mice that responded to αTIGIT and bintrafusp alfa combination therapy generated memory responses and were protected from rechallenge. These effects were dependent on CD4 + and CD8 + T cells, as well as increased immune infiltration into the TME. This combination induced production of tumor-specific CD8 + T cells, and an increase in activation and cytotoxicity resulting in an overall activated immune landscape in the tumor. Data presented herein demonstrate the αTIGIT and bintrafusp alfa combination has efficacy across multiple tumor models, including the checkpoint-resistant model of murine colon carcinoma, MC38-CEA and the HPV + model TC-1.